BENTUK DEIKSIS DALAM FILM “NANTI KITA CERITAKAN TENTANG HARI INI” KARYA MARCHELLA (KAJIAN PRAGMATIK) - Kartika Dewi Wulandari; Sainil Amral; Supriyati Supriyati (Universitas Batanghari, 2024)
The aim of this research is to describe the use of deixis forms in the film Nanti Kita Cerita Tentang Hari Ini karya Marchella. This research is a qualitative descriptive study. The data in this research is in the form of dialogue utterances in which there is the use of person deixis, place deixis, and time deixis in the film Nanti Kita Cerita Tentang Hari Ini karya Marchella. The results of this research can be concluded that there are findings in the form of utterances related to the 3 forms of deixis in the film Nanti Kita Cerita Tentang Hari Ini karya Marchella. The three forms of deixis are (1) Persona Deixis, (2) Place Deixis, and (3) Time Deixis. Of the three forms of deixis, 242 utterances were found that contained the use of deixis. The most dominant quotation found in this film is the use of person deixis in 212 utterances, and the least found is place deixis in 9 utterances.